Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Sebagai Variabel Mediasi Terhadap Loyalitas Konsumen pada Caffe Ruang Hati di Sangatta - Eka Nurjannah; Wiwiek Neviana Yusuf; Nanda Dian Eka; Wasti Sa'dan; Syahril Hasan (MES Bogor, 2026)
This study aims to analyze the effect of service quality and price on customer satisfaction and customer loyalty, with satisfaction acting as a mediating variable at Caffe Ruang Hati in Sangatta. This research adopts a quantitative approach with an associative design. Data were collected through questionnaires distributed to 180 respondents who are customers of Caffe Ruang Hati in Sangatta. The data analysis technique employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. The results indicate that service quality has a positive and significant effect on customer satisfaction and customer loyalty. Price is also found to have a positive and significant effect on customer satisfaction and customer loyalty. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty. The indirect effect analysis reveals that customer satisfaction significantly mediates the relationship between service quality and customer loyalty, as well as between price and customer loyalty. Overall, all proposed hypotheses are supported. These findings highlight that improving service quality and setting appropriate pricing strategies can enhance customer satisfaction, which in turn fosters stronger customer loyalty at Caffe Ruang Hati in Sangatta.